Does Mobile Money Use Increase Firms' Investment? : Evidence from Enterprise Surveys in Kenya, Uganda, and Tanzania - Islam, Asif; Muzi, Silvia; Rodriguez Meza, Jorge Luis (World Bank, Washington, DC, 2016)
Private investment can be an important engine of economic growth in East African countries, which, despite recent growth rates, are still plagued with adverse economic conditions. Against this backdrop, there has been substantial penetration of mobile money, moving beyond simple person-to-person exchanges toward adoption by private firms. This study explores whether there is a relationship between firm adoption of mobile money and firm investment. Using firm-level data that are nationally representative of the private sector in three East African countries -- Kenya, Tanzania, and Uganda -- a positive relationship is found between mobile money use and the probability of a firm’s purchase of fixed assets. This relationship is attributed to reduced transaction costs, increased liquidity, and increased credit worthiness associated with the use of mobile phone financial services.